Diagnostic Assessment of Islamic Education Learning in Merdeka Curriculum: A Systematic Review - Abdulloh Hadziq (Al-Misbah (Jurnal Islamic Studies), 2023)
Assessment is one of the important aspects of learning, not least in Islamic religious learning. Learning is both cognitive and non-cognitive. Assessment activities act as a measuring tool that races at each level of learner competence to improve learning outcomes and achieve learning objectives. Moreover, with the existence of the Merdeka Curriculum which emphasizes the interests, talents, and excellence of competencies possessed by students. Therefore, this study aims to determine the accuracy of diagnostic assessments in Islamic religious learning used in the Merdeka Curriculum. This research is a systematic literature review using the Google Scholar database and Semantic Scholar Search. Based on the findings, identifying the appropriate assessment carried out in the use of the Merdeka Curriculum in Islamic learning is a diagnostic assessment. In its application, the assessment has many results of consideration in measuring and improving the competence of students, so that there will be many solutions in directing students according to their ability level, especially in memorization and understanding. However, the implementation in the field still has several obstacles. This is the basis for the importance of further research to be carried out.